Environmental Transparency and Financial Success: The Mediating Influence of Carbon Emission Reporting - Bone, Esra Eban; Rahmadhani, Sari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This research aims to analyze the mediating role of carbon emission disclosure (CED) in the relationship between carbon performance (CP), green product innovation (GPI), environmental costs (EC), and the percentage of women directors (WBD) on green financial performance (FP). Using data from 66 energy sector companies listed on IDX-IC during 2021–2023, the study employs PLS-SEM path analysis to test its hypotheses. Results reveal that GPI, EC, and WBD positively impact FP, while CP does not. Similarly, CED is influenced by CP, GPI, and EC but not by WBD. The mediation test yields three key findings: first, WBD directly affects FP; second, CED partially mediates the relationships between GPI and FP, as well as EC and FP; third, CED fully mediates the link between CP and FP. The study underscores the significance of CED as a mediator, particularly in connecting CP with FP, highlighting environmental transparency as an effective strategy. Furthermore, the findings demonstrate that GPI and EC management directly enhance FP, while gender diversity on boards significantly drives green financial outcomes. Transparent CED compels companies to be more accountable for their environmental impacts, fostering improved environmental practices and financial performance through enhanced accountability.